Identifikasi Standar Kualitas Bahan Baku Sayuran Dalam Industri Perhotelan: Studi Kasus Di Labuan Bajo: Identification of Quality Standards for Vegetable Raw Materials in the Hospitality Industry: A Case Study in Labuan Bajo - Siagian, Reynaldo; Hibur, Tekla Ayuningsih (Program Studi Manajemen Divisi Kamar, 2025)
The hospitality industry, particularly in the food and beverage sector, relies heavily on the quality of raw materials to ensure guest satisfaction. One of the key ingredients that significantly influences the quality of dishes is vegetables, which must meet certain standards such as freshness, size, color, cleanliness, and food safety. This study aims to identify the quality standards for vegetable raw materials applied by hotels in Labuan Bajo, focusing on key vegetables such as potatoes, carrots, and lettuce, as well as understanding the origin of vegetable suppliers and the challenges faced in sourcing these raw materials. Based on interviews, observations, and documentation with hotel staff in Labuan Bajo, the results show that most hotels rely on suppliers from outside the region, though they still strive to support local suppliers. The three hotels studied established strict criteria for vegetable quality, including freshness, size, color, cleanliness, and food safety. Proper packaging and storage are also essential factors in maintaining vegetable quality. This research is expected to provide insights for local suppliers to improve the quality of their products and assist hotels in obtaining high-quality vegetable supplies that can better meet guest needs.